2015
DOI: 10.1007/s00101-015-0010-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapie des akuten Lungenversagens

Abstract: Lung protective ventilation with reduced tidal volumes as well as inspiratory pressures represents the current standard of care and was utilized in all network centers. Prone positioning was widely used. Promising adjuvant therapies such as the muscle relaxation during the early phase of the ARDS, fluid restriction and corticosteroids were used less frequently. During ECMO respirator therapy was generally continued with ultraprotective ventilator settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…However, deep sedation is required in patients with ARDS who receive neuromuscular blockage to ensure patients do not consciously experience paralysis. 34,35 Neuromuscular blockage is sometimes used in severe ARDS based on results of a multicenter trial in France that showed improved mortality with 48 hours of neuromuscular blockage in patients who have severe hypoxemia (PaO 2 /FiO 2 ratio<150) early during their ARDS. 36 A large, multicenter trial (NCT02509078) is now underway in the United States (US) to rigorously test whether early neuromuscular blockade results in better outcomes for patients with severe ARDS compared to current standard of care approaches, including light sedation.…”
Section: Minimizing Sedationmentioning
confidence: 99%
“…However, deep sedation is required in patients with ARDS who receive neuromuscular blockage to ensure patients do not consciously experience paralysis. 34,35 Neuromuscular blockage is sometimes used in severe ARDS based on results of a multicenter trial in France that showed improved mortality with 48 hours of neuromuscular blockage in patients who have severe hypoxemia (PaO 2 /FiO 2 ratio<150) early during their ARDS. 36 A large, multicenter trial (NCT02509078) is now underway in the United States (US) to rigorously test whether early neuromuscular blockade results in better outcomes for patients with severe ARDS compared to current standard of care approaches, including light sedation.…”
Section: Minimizing Sedationmentioning
confidence: 99%
“…La sepsis es una infección generalizada caracterizada por una inflamación sistémica en la cual los pacientes que la padecen llegan a presentar LPA leve y aunque no cumplan con los criterios de SIRA requieren de AMV, 2,6,7 con estrategias de protección pulmonar para evitar la progresión del mismo; pero si no se lleva a cabo de forma apropiada puede ocasionar VILI. 10 Hasta la fecha no existe un modo ventilatorio en específico para ser utilizado en la terapia de la sepsis, 10 ya que se ha demostrado que los modos ventilatorios más utilizados (VCV y VCP) 11 pueden dañar la arquitectura pulmonar, la función y la hemodinamia; 12,13 por lo que es necesario buscar y adecuar nuevos modos ventilatorios que eviten esto y no incrementen las lesiones pulmonares ocasionadas por la inflamación sistémica inducida por la sepsis. Con base en lo anterior, el objetivo de este estudio fue comparar el efecto de la AMV en modo VCP, APRV y VAFO como única terapia sobre la hemodinamia, gasometría, mecánica e histología pulmonar en un modelo porcino de inflamación sistémica inducida por LPS E. coli.…”
Section: Discussionunclassified
“…10 Los modos ventilatorios comúnmente utilizados durante la sepsis y el SIRA son la ventilación controlada por volumen (VCV) y la ventilación controlada por presión (VCP). 11 No obstante, estudios clínicos y experimentales han demostrado que estos modos ventilatorios pueden dañar la función y la arquitectura pulmonar, así como la hemodinamia. 12,13 Por tanto, es necesario buscar y adecuar otros modos ventilatorios que eviten esto y no incrementen las lesiones pulmonares ocasionadas por la inflamación sistémica inducida por la sepsis.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Compared with iNO, inhaled prostanoids require no special application and monitoring equipment, and are therefore easier and less expensive to administer. This could be the reason for the increase in use over time in the treatment of ARDS [33], although there is no clinical data showing a mortality benefit and large scale randomized clinical trials (RCTs) are lacking [34]. In a meta-analysis in 2015, Fuller et al [34] demonstrate that inhaled prostaglandins improve oxygenation and decrease pulmonary artery pressures.…”
Section: Introductionmentioning
confidence: 99%